2013
DOI: 10.3906/kim-1302-74
|View full text |Cite
|
Sign up to set email alerts
|

An expedient synthesis of 6-Vinylfulvene

Abstract: 6-Vinylfulvenes constitute a class of fulvenes that are difficult to access due to the lack of a general method for their synthesis. In particular, the unsubstituted parent system has been very difficult to obtain by existing methods.In this communication we describe a convenient 3-step protocol for the synthesis of the title compound by way of sulfide oxidation and subsequent sulfoxide elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…To avoid this, they devised a one-pot synthesis of utilizing a sulfide oxidation and subsequent sulfoxide elimination strategy. 63 This protocol offers an excellent strategy for the synthesis of unsubstituted and substituted 6-vinylfulvene (Scheme 4).…”
Section: Extension Of Conventional Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…To avoid this, they devised a one-pot synthesis of utilizing a sulfide oxidation and subsequent sulfoxide elimination strategy. 63 This protocol offers an excellent strategy for the synthesis of unsubstituted and substituted 6-vinylfulvene (Scheme 4).…”
Section: Extension Of Conventional Methodsmentioning
confidence: 97%
“…An exceptionally simple and efficient synthesis of 6-methyl-6-vinylfulvene 21 was developed by Erden and Gärtner (Scheme ). Later, the authors devised a convenient three-step protocol utilizing a sulfide oxidation and subsequent sulfoxide elimination strategy . This protocol offers an excellent strategy for the synthesis of unsubstituted and substituted 6-vinylfulvene (Scheme ).…”
Section: Synthesis Of Pentafulvenesmentioning
confidence: 99%
“…Fulvenes constitute a fascinating class of cross-conjugated olefins, and since their first synthesis by Thiele in 1900 1 they have commanded considerable interest due their diverse reactivities. 2 Our own efforts in this area focused mainly on the development of new methods for their synthesis, 3 6 their cycloaddition chemistry, and in particular, their reactions with singlet oxygen. 7 11 In the course of our studies, we found that the fulvenyl unit exerts a considerable electron-withdrawing effect on alkyl, aryl, and vinyl groups attached to the exocyclic double bond (C6), though our findings have been qualitative to date.…”
Section: Introductionmentioning
confidence: 99%
“…The reported yield across the three steps was 37% including a purification after each step. 26 Kaiser and Hafner showed that 6-(2-aminovinyl)fulvenes would undergo a solution-phase thermal cyclisation and isomerisation in boiling piperidine to give 3-amino-PnH 2 in high yields (Fig. 9).…”
Section: Thermal Cyclisations Of Vinyl Fulvenesmentioning
confidence: 99%